Comparative study of diurnal and nocturnal sap flow of Quercus ilex and Phillyrea latifolia in a Mediterranean holm oak forest in Prades (Catalonia, NE Spain) - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (Trees, 2012)
Droughts are a cyclical disturbance in Mediterranean ecosystems and climate change models forecast an increase of their frequency and severity. Some experimental and observational studies have shown that cooccurring species may cope with drier conditions with different strategies and present different responses. Here, we investigate sap ﬂow response to drought in order to explain the observed differential growth and mortality of Quercus ilex and Phillyrea latifolia at Prades Holm oak forest (NE Spain). We measured sap ﬂow of these species and compared their diurnal, nocturnal and seasonal patterns and their relationship with environmental variables. Both species described qualitatively similar daily patterns, either during daylight or night. Sap ﬂow rates were signiﬁcantly higher in P. latifolia except in autumn and spring. P. latifolia was more sensitive to soil moisture. Nocturnal sap ﬂow was detected in both species with no signiﬁcant differences and hourly rates suffered a progressive increase from 3 a.m. to dawn in most sampled nights. Our results indicate a better adaptation of P. latifolia to this site as it can take better advantage of wet periods while maintaining higher sap ﬂow rates during dry periods. Along with previous ecophysiological studies at the same location it may be inferred that at its drier distributional limit Q. ilex would be at disadvantage with respect to other species like P. latifolia, as the latter would cope better with increasing xeric conditions already occurring and further predicted for Mediterranean ecosystems. Our results also show nocturnal sap ﬂow to be relevant in individual water losses in these two species as they can be up to 35–40 % of daily sap ﬂow. Further research on the underlying mechanisms of this nocturnal sap ﬂow is required since it may also enhance early morning CO2 ﬁxation or nutrient supply to leaves.
Keywords: á; Drought; ilex á sap flow; nocturnal sap flow; nocturnal sap flow á; phillyrea latifolia; phillyrea latifolia á quercus; Quercus ilex; sap flow

Optimization of dry-season sap flow measurements in an oak semi-arid open woodland in Spain - Reyes-Acosta, J Leonardo; Lubczynski, Maciek W (Ecohydrology, 2012)
In sap flow studies, there is no method complying with high efficiency and versatility of sap flow measurements. To improve that, we propose combining two methods: (1) thermal dissipation probe (TDP) known to be efficient and cost effective and (2) heat field deformation (HFD) known to be versatile. For that purpose, we used a step-wise TDP sap flux density (Jp) optimization method consisting of (1) natural temperature gradient (NTG) correction applying the cyclic heat dissipation (CHD) method, (2) night flow ΔTmax correction using HFD data as reference and (3) radial-azimuthal correction using HFD as reference. We applied this optimization method on Quercus ilex (Q.i.) and Quercus pyrenaica (Q.p.) trees in a Spanish semi-arid open woodland during dry season. The NTG correction resulted in substantial reduction of Jp as compared with standard TDP. The subsequent ΔTmax night flow correction resulted in the increase of NTG-corrected Jp and good agreement with the outermost 2 cm of HFD measurements for both species. The final radial-azimuthal adjustment of TDP Jp resulted not only, in a good agreement with HFD Jp, but also provided novel ecohydrological insights such as: (1) evidence of continuous night flow in all Q.p. trees and some Q.i. trees, (2) exponential reduction of Jp with sapwood depth for both species, (3) significantly larger Jp in the outermost 1 cm of sapwood for Q.p. than for Q.i. and (4) high azimuthal Jp variability for both species. The presented study offers efficient and versatile method of tree sap flow measurements that contributed to a better understanding of water-related dynamics of Q.i. and Q.p. under water-stress conditions. Copyright © 2012 John Wiley & Sons, Ltd.
Keywords: HFD; natural temperature gradient; Quercus ilex; Quercus pyrenaica; radial and azimuthal sap flow variability; sap flow; semi-arid open forest; TDP

Impact of stand density on water status and leaf gas exchange in Quercus ilex - Moreno, Gerardo; Cubera, Elena (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning
Keywords: leaf water potential; open woodland; photosynthesis; sap flow; Soil moisture

Impact of stand density on water status and leaf gas exchange in Quercus ilex - Moreno, Gerardo; Cubera, Elena (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning
Keywords: leaf water potential; open woodland; photosynthesis; sap flow; Soil moisture

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl237
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl23710.1093/jxb/erl237The following values have no corresponding Zotero field: accession-num: 17229759
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Water-use strategies in two co-occurring Mediterranean evergreen oaks: surviving the summer drought - David, T. S.; Henriques, M. O.; Kurz-Besson, C.; Nunes, J.; Valente, F.; Vaz, M.; Pereira, J. S.; Siegwolf, R.; Chaves, M. M.; Gazarini, L. C.; David, J. S. (Tree Physiology, 2007)
In the Mediterranean evergreen oak woodlands of southern Portugal, the main tree species are Quercus ilex ssp. rotundifolia Lam. (holm oak) and Quercus suber L. (cork oak). We studied a savannah-type woodland where these species coexist, with the aim of better understanding the mechanisms of tree adaptation to seasonal drought. In both species, seasonal variations in transpiration and predawn leaf water potential showed a maximum in spring followed by a decline through the rainless summer and a recovery with autumn rainfall. Although the observed decrease in predawn leaf water potential in summer indicates soil water depletion, trees maintained transpiration rates above 0.7 mm day−1 during the summer drought. By that time, more than 70% of the transpired water was being taken from groundwater sources. The daily fluctuations in soil water content suggest that some root uptake of groundwater was mediated through the upper soil layers by hydraulic lift. During the dry season, Q. ilex maintained higher predawn leaf water potentials, canopy conductances and transpiration rates than Q. suber. The higher water status of Q. ilex was likely associated with their deeper root systems compared with Q. suber. Whole-tree hydraulic conductance and minimum midday leaf water potential were lower in Q. ilex, indicating that Q. ilex was more tolerant to drought than Q. suber. Overall, Q. ilex seemed to have more effective drought avoidance and drought tolerance mechanisms than Q. suber.
10.1093/treephys/27.6.79310.1093/treephys/27.6.793
Keywords: canopy conductance; groundwater; Hydraulic conductance; leaf water potential; Quercus ilex; Quercus suber; sap flow

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances

Transpiration and stomatal behaviour of Quercus ilex plants during the summer in a Mediterranean carbon dioxide spring - Tognetti, R; Longobucco, A; Miglietta, F; Raschi, A (Plant, Cell & Environment, 1998)
Variations in the water relations and stomatal response of Quercus ilex were analysed under field conditions by comparing trees at two locations in a Mediterranean environment during two consecutive summers (1993 and 1994). We used the heat-pulse velocity technique to estimate transpirational water use of trees during a 5 month period from June to November 1994. At the end of sap flow measurements, the trees were harvested, and the foliage and sapwood area measured. A distinct environmental gradient exists between the two sites with higher atmospheric CO2 concentrations in the proximity of a natural CO2 spring. Trees at the spring site have been growing for generations in elevated atmospheric CO2 concentrations. At both sites, maximum leaf conductance was related to predawn shoot water potential. The effects of water deficits on water relations and whole-plant transpiration during the summer drought were severe. Leaf conductance and water potential recovered after major rainfall in September to predrought values. Sap flow, leaf conductance and predawn water potential decreased in parallel with increases in hydraulic resistance, reaching a minimum in mid-summer. These relationships are in agreement with the hypothesis of the stomatal control of transpiration to prevent desiccation damage but also to avoid ‘runaway embolism’. Trees at the CO2 spring underwent less reduction in hydraulic resistance for a given value of predawn water potential. The decrease in leaf conductance caused by elevated CO2 was limited and tended to be less at high than at low atmospheric vapour pressure deficit. Mean (and diurnal) sap flux were consistently higher in the control site trees than in the CO2 spring trees. The degree of reduction in water use between the two sites varied among the summer periods. The control site trees had consistently higher sap flow at corresponding values of either sapwood cross-sectional area or foliage area. Larger trees displayed smaller differences than smaller trees, between the control and the CO2 spring trees. A strong association between foliage area and sapwood cross-sectional area was found in both the control and the CO2 spring trees, the latter supporting a smaller foliage area at the corresponding sapwood stem cross-sectional area. The specific leaf area (SLA) of the foliage was not influenced by site. The results are discussed in terms of the effects of elevated CO2 on plant water use at the organ and whole-tree scale.
Keywords: Drought; Mediterranean; natural CO2 springs; Quercus ilex; sap flow; Stomatal conductance; water relations

Micrometeorological assessment of sensitivity of canopy resistance to vapour pressure deficit in a Mediterranean oak forest - Pitacco, A; Gallinaro, N (Ann. For. Sci., 1996)
Canopy surface resistance to water vapour (rc) of an extensive Quercus ilex L stand (Bosco Mesola, northeast Italy) has been evaluated by inverting the Penman-Monteith equation. The latent heat flux was estimated by applying the Bowen ratio-energy budget micrometeorological method. A linear relationship was found between rc and the vapour pressure deficit. Canopy resistance increased regularly during the day and that yielded a recurring diurnal pattern of energy partitioning where most of the latent heat was dissipated in the early morning and the release of sensible heat increased after midday. This behaviour has been confirmed also by independent estimates of transpiration, based on measurements of sap flow velocity in small branches. Ecological consequences of this feature are briefly discussed applying the concept of coupling between canopy and atmosphere
Keywords: canopy resistance; energy balance; Evapotranspiration; Quercus ilex L; sap flow

Water relations of oak species growing in the natural CO2 spring of Rapolano (central Italy) - Tognetti, R; Giovannelli, A; Longobucco, A; Miglietta, F; Raschi, A (Ann. For. Sci., 1996)
The effect of elevated atmospheric carbon dioxide on water relations was examined on downy oak (Quercus pubescens) and holm oak (Q ilex) trees. The study was conducted on trees growing in a naturally enriched CO2 spring. Sap velocity and sap flow were measured by the heat pulse technique. On the same trees, daily courses of xylem water potential, leaf conductance and transpiration were monitored. Plant water relations were evaluated by pressure-volume analysis method on shoots; on the same branches, relative conductivity of xylem was measured. Both species exhibited increased osmotic potential and decreased symplasmic fraction of water in trees adapted to increased CO2. Downy oak showed lower stomatal conductance under elevated CO2, but holm oak did not. Both species displayed higher sap flow in control trees. In both species, increased carbon dioxide did not influence xylem embolism formation.
Keywords: Drought; Elevated CO2; embolism; Quercus ilex; Quercus pubescens; sap flow; water relations